2017
DOI: 10.1038/s41598-017-00927-w
|View full text |Cite
|
Sign up to set email alerts
|

Moderate plasma dilution using artificial plasma expanders shifts the haemostatic balance to hypercoagulation

Abstract: Artificial plasma expanders (PEs) are widely used in modern transfusion medicine. PEs do not contain components of the coagulation system, so their infusion in large volumes causes haemodilution and affects haemostasis. However, the existing information on this effect is contradictory. We studied the effect of the very process of plasma dilution on coagulation and tested the hypothesis that moderate dilution with a PE should accelerate clotting owing to a decrease in concentration of coagulation inhibitors. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
0
7
0
1
Order By: Relevance
“…Так как измерение отдельных факторов эндогенного фибринолиза имеет много неоднозначных [8,9]. Нами были получены данные, что процесс тромбообразования, так же, как и процесс лизиса тромба активнее протекает у пациентов с ОКС по сравнению со здоровыми добровольцами.…”
Section: Discussionunclassified
“…Так как измерение отдельных факторов эндогенного фибринолиза имеет много неоднозначных [8,9]. Нами были получены данные, что процесс тромбообразования, так же, как и процесс лизиса тромба активнее протекает у пациентов с ОКС по сравнению со здоровыми добровольцами.…”
Section: Discussionunclassified
“…70 They found that dilution progressively reduced the peak of thrombin generation; interestingly, in an experimental report, moderate hemodilution increased thrombin generation. 91 In these simulations hypothermia delayed the onset of thrombin generation and increased thrombin generation (both endogenous thrombin potential and thrombin peak). Another group used the legacy model to describe how changes in blood coagulation factor balance in human immunodeficiency virus patients shift the hemostasis to hypercoagulation, 92 or in patients with hemophilia C, 93 hemophilia A, 94 or deep vein thrombosis, 95 and what is the variation of thrombin generation in healthy individuals.…”
Section: Computer Models Of Blood Coagulation and Fibrinolysismentioning
confidence: 90%
“…For thrombin clotting time 100 µl of citrated plasma sample were incubated (for 15 min at 37 °C) with the same volume of diluent containing scalar concentrations of BDNF (0, 60 and 120 pg/ml) or BSA (1 mg/ml: control), then, 100 µl of human thrombin (1 U/ml; SIGMA-ALDRICH, St Louis, MO, USA) were added 39 .…”
Section: Methodsmentioning
confidence: 99%